Optimization Method for Centralized Transmission of Offshore Wind Power from Multiple Wind Farms - Sheng LIU (南方能源建设)
[Objective] The traditional research object of offshore wind power transmission is the point-to-point onshore transmission of electricity from a single wind farm, which has limitations, and the economic evaluation method used only considers initial investment, which is not systematic and scientific enough. In response to the current application scenarios of offshore wind power integrated development, this article proposes a method for optimizing the centralized transmission mode of multiple wind farms, guiding the determination of the optimal transmission scheme. [Method] Technically, according to the working principle, offshore wind power transmission includes three types: AC, DC, and AC DC hybrid, each with its own characteristics and scope of application. In terms of economy, in addition to initial investment, consideration should also be given to the losses, maintenance, shutdown losses, and costs incurred during the operation of the equipment over its service life, as well as the costs incurred during sea area leasing. Symmetric monopole systems and symmetrical bipolar systems should adopt different calculation methods based on system characteristics. [Result] This article provides six centralized transmission solutions for typical cases, covering all mainstream technical solutions for current AC and DC transmission. Select the optimal delivery plan by comparing the technical and economic aspects of different plans. [Conclusion] China's offshore wind power is currently moving from small-scale demonstration applications to large-scale integrated development. The optimal method for centralized transmission of offshore wind power from multiple wind farms proposed in this article is deeply in line with the market demand for large-scale centralized transmission of offshore wind power in the future, and has high guiding value.